Utilility of flow cytometry as ancillary study to improve the cytologic diagnosis of thyroid lymphomas. Issue 5 (27th November 2014) - Stacchini, Alessandra; Pacchioni, Donatella; Demurtas, Anna; Aliberti, Sabrina; Cassenti, Adele; Isolato, Giuseppe; Gazzera, Carlo; Veltri, Andrea; Sapino, Anna; Papotti, Mauro; Freddi, Milena; Palestini, Nicola; et al.
Abstract : Background: To evaluate the efficacy of the use of flow cytometry (FC) immunophenotyping together with fine‐needle aspiration cytology (FNAC) in the diagnosis of thyroid lymphoma. Methods: FC was performed in parallel with FNAC in 35 samples of suspected thyroid lymphoma over a 12 years period. Results were correlated with histological or molecular findings and follow‐up, when available. Results: A final diagnosis of lymphoma was given in 13 of 35 (37.1%) specimens. Among the 22 cases considered negative for lymphoma by FC, 11 were diagnosed as thyroiditis by cytology, 7 as reactive, 2 were anaplastic carcinoma, and 2 cases were considered cytologically suspicious for lymphoma but were not confirmed by further investigations. Histology on core biopsy or molecular analysis was available in 12 of 13 lymphoma cases (92.3%). Data obtained by the combination cytology/FC were confirmed in all cases on histology biopsies. Correlation with histology showed a sensitivity and a specificity of 100% for the combination cytology/FC. Conclusions: FC is an important additional test that can contribute with cytology to the identification of lymphomas of the thyroid. FC can detect the presence of small neoplastic lymphocyte populations and may contribute to the diagnosis of cases in which the lymphoid infiltrate is difficult to interpret on cytology alone. © 2014 International Clinical Cytometry Society